What difference does time make? : papers from the ancient and Islamic Middle East and China in honor of the 100th anniversary of the Midwest Branch of the American Oriental Society - Scurlock, Jo Ann, 1953-; Beal, Richard Henry, 1953- (Archaeopress ancient Near Eastern archaeology, 2019)
Proceedings of a conference held at St. Mary's University in Notre Dame, Indiana, in 2017, this volume presents a wide-ranging exploration of Time as experienced and contemplated. Included are offerings on ancient Mesopotamian archaeology, literature and religion, Biblical texts and archaeology, Chinese literature and philosophy, and Islamic law.